Pengaruh Konsumsi Air dan Keberadaan Fasilitas Sanitasi terhadap Angka Diare pada Anak-Anak di Indonesia - Nadia Nasyia Fahira; Estro Dariatno Sihaloho; Adiatma Yudistira Manogar Siregar (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: As a developing country, Indonesia maintains a low level of welfare for hygiene, as exemplified by Indonesia’s poor access facilities to clean water and lack of proper sanitation for households. Meanwhile, a proper supply of water and sanitation will help in reducing morbidity and mortality rates of diarrhea in children. Other risk factors such as socio-economic and socio-demographic conditions, helps improving the quality of life of households, thus lowering the risk of various diseases, including diarrhea.Methods: This study uses a Logistic Regression Analysis (Logit) model with Cross-sectional design using data collected from the 5th wave of the Indonesian Family Life Survey (IFLS-5) in 2014. The study population was children aged 2-10 years with a total of 2446 observations.Result: The result shows that there was a relationship between father's education in elementary school level (p=0.013), father's education in junior high school level (p=0.015), father's education in high school level (p=0.001), father's education at the university level (p=0.012), income (p=0.051), children’s age (p=0.000), and children’s gender (p=0.033) with the rate of diarrhea in children.Conclusion: This research concludes that water consumption factors (sources of drinking water, drinking water boiling process before consumption) and sanitation facilities factors (household toilet types) have insignificant results on the diarrhea rate of children in urban areas of Indonesia. However, socio-economic factors (fathers' education and household income) and socio-demographic factors (children’s gender and children’s age) have a significant effect on the diarrhea rates of children in urban areas of Indonesia.